Spatial variations of community structures and methane cycling across a transect of Lei-Gong-Hou mud volcanoes in eastern Taiwan - Wang, Pei-Ling; Chiu, Yi-Ping; Cheng, Ting-Wen; Chang, Yung-Hsin; Tu, Wei-Xain; Lin, Li-Hung (Frontiers in Microbiology, 2014)
This study analyzed cored sediments retrieved from sites distributed across a transect of the Lei-Gong-Hou mud volcanoes in eastern Taiwan to uncover the spatial distributions of biogeochemical processes and community assemblages involved in methane cycling. The profiles of methane concentration and carbon isotopic composition revealed various orders of the predominance of specific methane-related metabolisms along depth. At a site proximal to the bubbling pool, the methanogenic zone was sandwiched by the anaerobic methanotrophic zones. For two sites distributed toward the topographic depression, the methanogenic zone overlaid the anaerobic methanotrophic zone. The predominance of anaerobic methanotrophy at specific depth intervals is supported by the enhanced copy numbers of the ANME-2a 16S rRNA gene and coincides with high dissolved Fe/Mn concentrations and copy numbers of the Desulfuromonas/Pelobacter 16S rRNA gene. Assemblages of 16S rRNA and mcrA genes revealed that methanogenesis was mediated by Methanococcoides and Methanosarcina. pmoA genes and a few 16S rRNA genes related to aerobic methanotrophs were detected in limited numbers of subsurface samples. While dissolved Fe/Mn signifies the presence of anaerobic metabolisms near the surface, the correlations between geochemical characteristics and gene abundances, and the absence of aerobic methanotrophs in top sediments suggest that anaerobic methanotrophy is potentially dependent on iron/manganese reduction and dominates over aerobic methanotrophy for the removal of methane produced in situ or from a deep source. Near-surface methanogenesis contributes to the methane emissions from mud platform. The alternating arrangements of methanogenic and methanotrophic zones at different sites suggest that the interactions between mud deposition, evaporation, oxidation and fluid transport modulate the assemblages of microbial communities and methane cycling in different compartments of terrestrial mud volcanoes.